2020
DOI: 10.1007/s40520-020-01537-9
|View full text |Cite
|
Sign up to set email alerts
|

Impaired breathing, sleeping, vitality, and depression, and negative impact of L-T4 treatment characterize health-related quality of life in older people with stable CVD

Abstract: Background Cardiovascular disease (CVD) and thyroid dysfunction are common in older people, but little is known about how they affect health-related quality of life (HRQoL). Methods We assessed HRQoL with the 15D instrument in 329 home-dwelling patients aged ≥ 75 years with stable CVD and compared the results to those of an age-and gender-matched general population (n = 103). We also studied the impact of age, BMI, number of medications, thyroid-stimulating hormone (TSH) concentration, levothyroxine (L-T4) sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
1
3
1
Order By: Relevance
“…I‐QOL sub‐dimension and total scores determined by Lateef et al are similar to the results obtained in the present study 37 . Although the sub‐dimension mean scores were higher in the study of Ojala et al, the mean total score was similar 38 . These results indicate that incontinence is a problem that negatively affects the quality of life socially, behaviourally, and psychologically.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…I‐QOL sub‐dimension and total scores determined by Lateef et al are similar to the results obtained in the present study 37 . Although the sub‐dimension mean scores were higher in the study of Ojala et al, the mean total score was similar 38 . These results indicate that incontinence is a problem that negatively affects the quality of life socially, behaviourally, and psychologically.…”
Section: Discussionsupporting
confidence: 89%
“…37 Although the sub-dimension mean scores were higher in the study of Ojala et al, the mean total score was similar. 38 These results indicate that incontinence is a problem that negatively affects the quality of life socially, behaviourally, and psychologically.…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, patients with CAD had slightly higher HRQoL (0.862) compared with previous studies (0.777–0.859) [ 6 , 28–31 ] using 15D. In the previous follow-up studies with patients receiving optimal drug or operative treatment, the HRQoL increased [ 29–31 ].…”
Section: Discussioncontrasting
confidence: 62%
“…flowchart), we can assume that patients had moderately stable disease. Previous studies have shown a decrease in HRQoL in cardiovascular disease patients if the disease is symptomatic or more severe [ 11 , 32 ], with depression, anxiety or hostility [ 2 , 11 , 32 , 37 ], higher BMI [ 28 ], age [ 11 , 28 ], number of cardiovascular risks and female gender [ 11 ]. The increase in HRQoL has been demonstrated with effective treatment [ 30 ], higher patient education [ 11 , 32 ], marital status and social support [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tools from the Health state descriptive system have been used in multiple studies, to monitor HRQoL in drug clinical research (Huoponen et al, 2020 ; Ojala, Sintonen, Roine, Strandberg, & Schalin-Jantti, 2020 ), following surgery (Ho et al, 2020 ; Vannas, Farkkila, Sintonen, Aberg, & Isoniemi, 2020 ), during rehabilitation (Roine et al, 2020 ) and in various conditions such as asthma (Ilmarinen et al, 2019 ; Rutishauser, Sawyer, & Bowes, 1998 ), diabetes (Karamanakos et al, 2019 ), renal transplantation (Qvist et al, 2004 ), cancer (Toija, Kettunen, Leidenius, Vainiola, & Roine, 2019 ), and mental illness (Granö, Karjalainen, Suominen, & Roine, 2011 ). The adult version (15D) is already available in multiple languages including French.…”
Section: Introductionmentioning
confidence: 99%